Investigating genome engineering of myotonic dystrophy cells and small molecules as potential therapeutic agents - López Morató, Marta (2018)
Myotonic dystrophy (DM) is a dominantly inherited multisystem disease. There are 2 types of DM: DM1, caused by a CTG repeat expansion in the 3’-UTR of the DMPK gene, and DM2, caused by a CCTG repeat expansion in intron 1 of the CNBP gene. In both types of DM the transcribed RNA, containing the repeat expansions, accumulate in the nucleus and sequester alternative splicing factors, such as MBNL1 proteins, causing the missplicing of many genes and contributing to the disease pathogenesis. These aggregations accumulate in the nucleus in the form of foci and represent a key target for therapeutic development.